TEKNIK MEMAINKAN ALAT MUSIK PUPUIK BATANG PADI OLEH AZWIR RAJO BONSU Di NAGARI KOTO ANAU - Adi Suhendra; Wimbrayardi Wimbrayardi; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2014)
Abstract The purpose of this research was to describe and find the Techniques of playing Pupuik Batang Padi. This research was conducted by using descriptive qualitative method.The research found the Technique of playing Pupuik Batang Padi performed by Rajo Bonsu Azwir.In this technique, the air was inhealed through the nose and would produced continuos sound when Pupuik Batang Padi was blown. Furthermore, in playing the melody, the higher the instrument blown, the lowder the sound produced. And the Three level of Direction were made of resonators. Kata kunci: Pupuik Batang Padi, Rajo Bonsu Azwir.